IDENTIFIKASI SENYAWA FITOKIMIA DAN DAYA ANTIMIKROBA EKSTRAK REMPAH UTAMA BUMBU-BUMBU RENDANG TERHADAP Staphylococcus aureus - Wellya lina (Jurnal Pertanian UMSB: Penelitian dan Kajian Ilmiah Bidang Pertanian, 2017)
This study aims to determine the phytochemical compounds which found inspices used in the making of rendang, knowing the chemical components of the mainspices of rendang, and determine the ability of antimicrobial in each of rendangseasoning. The result of analysis proved that there phytochemical compounds. (1) Thesecompounds are phenolic, alkaloids, flavonoids, terpenoids, steroids, and saponins.These compounds have funtion to determine the main chemical components in theextract constituent rendang spices that are known as antimicrobial power. (2) Theamount of the chemical components is obtained successively in marinades rendang suchas onion (2695,5 ppm inulin), red pepper (494,5 ppm capsaicin), turmeric leaf (2,057ppm curcumin), cumin (2152,2 ppm safranal), and ginger (1,07 % sineol). (3) Inhibitionof the extract seasoning against Staphylococcus aureus has a diameter that tend to beresistant among the onion (20 mm), red paper (17 mm), cumin (18 mm), and galangal(14 mm).Key word : phytochemical; antimicrobial; spices; rendang; Staphylococcus aureus